IMPROVEMENT OF ABILITY TO MAKE SENTENCES THROUGH MEDIA IMAGES OF CLASS III STUDENTS OF SDN 1 LAPAI NGAPA DISTRICT KOLAKA UTARA REGENCY (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This research is based on the background of the problem of Indonesian language learning outcomes that are still low, especially composing sentences quickly and precisely in class III SDN 1 Lapai, Ngapa District, North Kolaka Regency. Based on the results of field observations, it was found that there were some students who were unable to compose sentences correctly. Teachers in teaching Indonesian only ask students to read and copy sentences in the textbooks used, the teacher never prepares drawing media to help children compose sentences and rarely asks children to compose sentences. The teacher also never asks children to compose sentences based on their daily habits, children feel they do not need to compose sentences correctly. The research method used is Classroom Action Research (PTK) method. This research was carried out in two cycles. In this study, researchers used instruments in the form of tests, observation sheets, field notes, documentation and interviews. Data analysis was carried out with quantitative and qualitative techniques. Quantitative data is done by searching for an average, while qualitative dat is processed descriptively. Judging from the results of the ability to write speech texts, each cycle has increased. This is evident from the average value of composing sentences obtained by students from each cycle. Cycle I: 6.85 and Cycle II: 8.35. Thus researchers recommend to you to use image media as a solution to improve the ability to compose sentences quickly and precisely.